2015
DOI: 10.7883/yoken.jjid.2013.062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria among Acute Febrile Patients Clinically Suspected of Having Malaria in the Zeway Health Center, Ethiopia

Abstract: SUMMARY: Malaria diagnosis is a common challenge in developing countries with limited diagnostic services. Common febrile illnesses were assessed in 280 malaria-suspected patients, and each case was subjected to clinical and laboratory examinations for malaria, relapsing fever, typhoid fever, typhus, and brucellosis. Data were entered and analyzed using Epi Info version 3.1 software. Malaria accounted for 17z (CI, 12.6-21.4z) of febrile illnesses. The remaining cases were associated with typhoid fever (18.5z; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
(23 reference statements)
4
16
5
1
Order By: Relevance
“…falciparum infection by microscopy. This result is in line with previous health facility based studies in other parts of Ethiopia on causes of febrile illnesses [ 18 , 19 ], and the highest disease prevalence was found for typhus (14.0%) followed by typhoid fever (7.3%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…falciparum infection by microscopy. This result is in line with previous health facility based studies in other parts of Ethiopia on causes of febrile illnesses [ 18 , 19 ], and the highest disease prevalence was found for typhus (14.0%) followed by typhoid fever (7.3%).…”
Section: Discussionsupporting
confidence: 91%
“…However, the sero-prevalence of Rickettsia infection in this study was lower than the one reported from other parts of Ethiopia [ 19 , 28 ], but higher than the findings of the studies by Tadesse and Tadesse [ 18 ] and Birhane et al [ 29 ]. The variation might be linked to the type of environment in the study area.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Également, le caractère multifactoriel des déterminants de maladies en plus des facteurs environnementaux vient brouiller l'établissement du lien de nature causale (Chevalier et al, 2003). Une fièvre, par exemple, peut être causée par de nombreuses maladies dont le paludisme, la dengue ou les maladies diarrhéiques (Feleke et al, 2015). Les difficultés concernent également les multiples définitions des variables de l'environnement (accès à l'eau de boisson, assainissement et hygiène) (Dos Santos et al, 2014).…”
Section: éTat Des Connaissances Sur Les Relations Entre L'environnemeunclassified